Quem mexeu no meu texto? observações sobre literatura e sua adaptação para outros suportes textuais - Hattnher, Alvaro Luiz [UNESP] (My University, 2010)
The development in recent years of different media formats has boosted the consumption of narratives, generating a ‘narrative hunger’. Audiences have increasingly looked forward to absorb new and old narratives, and ‘adaptation’ has become a key operational concept to describe processes involved in the transformation of texts. Thus, our discussion will be centered around a few theoretical propositions on adaptation and appropriation in various textual architectures. Although relevant to the debate, literary canonical texts will not be the primary focus. Non-canonical texts will be used to re-visit concepts such as narrativization, intertextuality and transmediality and also to elaborate some ideas on interactivity and multimedia crossover.

O conceito de “adaptação” tem sido moeda corrente na circulação teórica associada a textos não canônicos, em especial ao binômio literatura/cinema. Este trabalho pretende rediscutir alguns aspectos relativos à relevância e operacionalidade desse conceito para os estudos comparados de estruturas narrativas em diversos suportes, tais como textos literários em suporte convencional, narrativas gráficas, narrativas cinematográficas e narrativas lúdicas interativas.
Keywords: adaptação; cinema; narratologia; narrativas não canônicas; transmidialidade; adaptation; cinema; transmedial narratology; noncanonic narratives